PROGRAM EVALUATION OF IMPLEMENTATION OF TECHNOLOGY, INFORMATION AND COMMUNICATION (ICT)-BASED LEARNING SYSTEMS IN MANAGEMENT PERSPECTIVE - Tipri Rose Kartika; Jamaludin Malik (Politeknik Negeri Media Kreatif, 2021)
Information and Communication Technology (ICT) is currently one of the media in the learning process at various levels of education. Through ICT, the learning process in the classroom can be carried out properly, especially by educators (teachers) and students (students). Thus, ICT becomes the main tool for interacting learning regardless of space and time. Information technology-based learning information systems can present interesting and interactive learning models. In order for the application of learning information systems to give good results, optimization of the management function is needed in each stage of its development. The stages of the management function that are very familiar to stakeholders in the education sector consist of: Planning, Organizing, Actuating and Controlling (POAC). With this management function, the application of learning information systems will be built and implemented properly. To measure the success of the implementation of this system, an evaluation of this educational program is needed. One of the most frequently used program evaluation models is the program evaluation model, the program evaluation model developed by Stufflebeam (Stufflebeam's Model), also known as the CIPP Model. Madrasah Tsanawiyah (MTS) Mathlaul Anwar Lampung is one of the schools under the auspices of the Ministry of Religion which also uses information technology as a medium in learning. In its application, the management function becomes the basis for MTS Mathlaul Anwar in building an information technology-based learning system.